Does body mass index affect atrial fibrillation ablation outcomes. (3rd October 2022) - Aleem, S; Al-Sadawi, M; Aslam, F; Ijaz, H; Cao, K; Jacob, R; Santore, L; Almasry, I; Fan, R; Rashba, E; Singh, A
Abstract: Background: There are conflicting reports in the literature regarding whether body-mass index (BMI) influences the success and procedural complication rates of atrial fibrillation (AF) ablation. Purpose: To determine if differences in BMI affect AF ablation outcomes Methods: At a single academic center, AF ablation procedures were reviewed from 2013 to 2021. Primary outcomes were AF recurrence (after a 90 day blanking period), procedure-related complications, emergency department visits or hospital admission (ED/HOSP). Patients had a minimum of 6 months follow-up Results: We analyzed 1569 AF ablation consecutive procedures (1093 de novo, 476 repeat ablation) using either radiofrequency or cryoablation. The study population was 65% male with a mean age 62 years, with 28% persistent AF. BMI was separated into three cohorts: <25 kg/m 2 (N=218), 25–30 kg/m 2 (N=547), and >30 kg/m 2 (N=804). There were no significant differences in the type of AF, left atrial diameter, or left ventricular ejection fraction in the BMI subgroups. There was a direct relationship between the prevalence of co-morbid conditions and increasing BMI: hypertension (49.1%, 59.9%, 60.2%; p 0.04), diabetes (6.4%, 13.5%, 21.3%; p 0.01), and obstructive sleep apnea (5.5%, 10.8%, 26.7%; p<0.01). There were no significant differences in AF recurrence, procedural complications or ED/HOSP among the BMI cohorts (p>0.05) (Figure 1). No gender related disparities were noted in outcomes (p>0.05). Conclusion: Higher BMI was not associated with AF recurrence, complications, or ED/HOSP after AF ablation despite a higher prevalence of comorbid medical conditions Funding Acknowledgement: Type of funding sources: None.